THE IMPLEMENTATION OF CLASSPOINT IN LEARNING ENGLISH: A CASE STUDY AT SMK MUHAMMADIYAH 3 KARANGANYAR ON ELEVENTH GRADE IN ACADEMIC YEAR 2021/2022 - Hidayat, Ikhwan Mahfud; Siregar, Epi Supriyani; Hasibuan, Siti Aminah; Ika Purnama Sari; Anggraini, Yanti (LPPM Universitas Negeri Jakarta, 2023)
The application of Information and Communication Technology (ICT) in teaching and learning activities has a major influence in improving the quality of education, especially in the era of the industrial revolution 4.0 as it is today. Classpoint is a learning platform that supports IT-based learning activities. This study aims to determine the application of Classpoints in learning English at SMK Muhammadiyah 3 Karanganyar on elevent grade in the academic year 2021/2022. The research approach is qualitative research, case study research. The method that used to collect data is observation, interviews, and documentation. The methods used to analyze the data are data reduction, data presentation, and drawing conclusions. To test the validity of the data used data triangulation, method triangulation, and source triangulation. The results of research on the three subjects can be seen that the application of classpoint is very effective for learning English